Students’ Perceptions on The Use of Learning Management System (LMS) in Phonology Course at The English Study Program - Syazwatika, Nurul; Noni, Nurdin; Korompot, Chairil Anwar (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This research aims to explore English students’ perceptions of the use of LMS (SYAM-OK) in Phonology courses as a facility to support their online learning process. The subjects of this research were 17 English students. Interviews were used as the main instruments in collecting data. The results of this research show that 17 students feel that they often use LMS (SYAM- OK) as a supporting tool in the online learning process in Phonology course. 17 English students thought that LMS (SYAM-O) was quite helpful in online learning, especially in filling in attendance, receiving learning materials, and collecting assignments. 17 English students have the same problem, namely connection problems when accessing the LMS (SYAM-OK), so they hoped for an LMS (SYAM-OK) in offline form only and features that they thought were important to add, such as voice notes and archives.